Prepulse Inhibition of the Tritonia Escape Swim - Mongeluzi, Donna L. (J Neurosci, 1998)
Presenting a weak stimulus just before a strong, startle stimulus reduces the amplitude of the ensuing startle response in humans and other vertebrates. This phenomenon, termed “prepulse inhibition” (PPI), appears to function to reduce distraction while processing sensory input. To date, no detailed neural mechanism has been described for PPI. Here we demonstrate PPI in the marine mollusk Tritonia diomedea, which has a nervous system highly suitable for cellular analyses. We found that a 100 msec vibrotactile prepulse prevented the animal’s escape swim response to a closely following 1 sec tail shock. This inhibition was highly transient, with a significant effect lasting just 2.5 sec. These findings indicate that the Tritoniaescape swim response undergoes a form of PPI phenomenologically similar to that observed in vertebrates. Further tests showed that the vibrotactile stimulus had no inhibitory effect if applied after tail shock, while the animal was preparing to swim, but it acted to terminate swims once they were actively under way. As a first step toward a cellular analysis of PPI, we recorded from neurons of the swim circuit in a semi-intact preparation and found that the vibrotactile stimulus used in the behavioral experiments also prevented the tail shock-elicited swim motor program. These results represent the first explicit demonstration of PPI in an invertebrate and establishTritonia as a model system for analyzing its physiological basis.